Meningkatkan Motorik Halus Anak Usia Dini Melalui Kegiatan Meronce - Farida farida; Chintya Aprilia Yanti (STAI Publisistik Thawalib Jakarta, 2023)
The aim of the research is to improve fine motor skills through ronce activities at Cendrawasih Sukmajaya Early Childhood Education. The research was carried out with classroom actions carried out in two subject cycles for 10 students. The results of observations of initial abilities in the pre-cycle showed that there were 7 children whose fine motor skills had not yet developed (70%) and 3 children who were starting to develop them (30%). In cycle I, there were 6 children who started to develop (60%) and 4 children (40%) who developed according to expectations. Then in cycle II, 2 children (20% of children) developed according to expectations and 8 children (80%) developed very well. This means that there is an increase in students' fine motor skills in implementing classroom action research. This research was stopped until cycle II because it had met the success indicator criteria. Conclusion: meronce activities can improve and increase fine motor skills, namely being able to follow the size of color patterns and students' work.